Study of the Shock Absorption Effectiveness of Air Cushions - Jacek Roguski; Leszek Jurecki; Ryszard Łyszczek; Krzysztof Cygańczuk (Safety & Fire Technology)
Aim: Safety air cushions play a key role in the Polish rescue system. The basic principles of operation of the jump cushion are based on controlled absorption of the kinetic energy of the human body falling from a great height. Thanks to the use of air layers and flexible energy-absorbing materials, the jump cushion is able to reduce the overload affecting the human body during contact with the shock-absorbing surface. The mechanism of impact overload during a fall involves a sudden deceleration and the accumulation of forces acting on the body, which creates a risk of injuries such as fractures, damage to internal organs or concussion. In order to ensure an optimal level of safety while minimising the risk of serious injuries to both rescuers and rescued people, it is important to understand the excessive deceleration mechanisms during a fall from a significant height. Safety air cushions are designed to slow the body down in a controlled manner by spreading kinetic energy over a larger surface area and for a longer period of time, which reduces the risk of serious injury. Typical g-forces on a well-designed air cushion are in the range of 5-10 g and exceeding them significantly increases the risk of injury. Methodology: series of experiments was conducted, where drop test manikins weighting 40 kg to 90 kg and equipped with accelerometers were thrown from height of 16 metres onto jump cushion targets. During these experiments, various jump cushions from different manufacturers with air-filled frames fed via air tanks were used. The data gathered together with video recordings of those tests were then thoroughly analysed. Conclusions: The research results established acceptable levels of g-force overload for the human body in specific boundary conditions. The data were confirmed consistent with the results accessible in the available literature and enabled the development of technical and operational requirements for safety cushions. The research emphasises the importance of refining the technical parameters of safety air cushions in order to ensure safety and minimise the risk of injuries during rescue operations. In the future, it may be necessary to conduct tests with a manikin of greater mass, which is dictated by the social tendency to gain weight, and to not limit falls to other places on the upper surface of the jump cushion, which may be significant for the magnitude of the overload occurring. Keywords: air cushion, jump cushion, biomechanical overload, air-filled frame, air cushions, impact (shock) absorption technologies